Optimized Energy-Aware Multipath Data Routing Framework for Underwater Wireless Sensor Networks in Marine Ecosystem and Species Health Monitoring Applications - Kiruthiga V, Narmatha V (South Eastern European Journal of Public Health, 2025)
Introduction: Underwater Wireless Sensor Networks (UWSNs) are becoming an increasingly important research area for exploring underwater resources, maintaining marine ecosystems, and monitoring species' health. Such UWSNs incorporate different types of sensor nodes deployed to monitor species' health, marine ecosystems, and other applications. The sensed data packets need to be directly routed to the floating sonobuoys for transferring the information to the monitoring station for further processing. Energy-efficient data routing with appropriate multipath in underwater acoustic channels is a challenging task. Objectives: To Design an effective routing protocol is required for efficient data packet routing and forwarding to overcome the challenges of underwater characteristics, providing better energy efficiency and a good packet delivery ratio. Methods: To overcome the challenges in existing routing protocols of UWSNs, this article proposes a novel Optimized Energy-Aware Multipath Data Routing Protocol (EA-MDRP). This proposed method considers depth, angle, and location-based information for selecting the most suitable next-hop neighbors for data packet forwarding and the routing phase. After completing the routing phase, the data packets are directly forwarded to the corresponding next-hop forwarders as per the priority table information. Results: For analysing the performance metrics, the packet delivery ratio (PDR), average end-to-end delay, and energy consumption are analyzed using MATLAB simulation. Conclusions: The proposed EEA-MDRP scheme achieves a better average end-to-end delay of 40 seconds, an improved packet delivery ratio of 57.5%, and 45.17 Joules of energy consumption compared to other existing state-of-the-art routing methods.